Neurociências e marketing: explorando fronteiras diádicas e integrando metodologias para a compreensão do comportamento do consumidor - Caissa Veloso e Sousa (2012)
In the last two decades of the XX century, especially at the begining of the XXI century the Neuroscience Showed expressive advances regarding the development and evaluation of the living brain, enabling one to capture the changes in braín functioning during mentalstimulation, using noninvasive techniques. Given these possibilities, other sciences beyond medical have expanding their chances of generating new knowledge through a multidisciplinary field of study. Speciflcally in regards to the behavioural intent of consumers,a new field of research have been emerging, expanding the possibilities of study which were predominant so tar, such as qualitative or quantitative research that utilise methods such as focal groups or structured interviews. This new field of study, named Neuromarketing", covers the development of techniques guided by the Neurosciences knowledge and the possibility of their use by Social Science professionals including scholars of human behaviour demonstrating advances in the understanding of latent needs of consumers, especially by identifying aspects of diffîcult expressions of knowledge by othcr research techniques. The research does not assume an absolute superiority of one metric over all others, but suggests more precise epistemological cuts; involving methodological aniculations both recent and well established ones. As an overall goal, the research is aimed at understanding the behaviour of car consumers, from the integration of methodologies applied to Neuro and Social Sciences. More specifically, the research aims at: (l) identify, through focal groups, aspects related to the decision making in the choice for a specific vehicle brand or model; (2) verify the segmentation criteria observed for the three car models studied; (3) analyse and compare the segmentation criteria for each car brand/model; (4) analyse the correlation brandprice for each car brand/model; (5) identity, by means of eye tracking,salient points for each car; (6) introduce an approach to identify, though eye tracking, thecardinal utility of tl1e three vehicles; (7) analyse the cardinal utility of tree FIAT Bravo advertisements; (8) offer subsidies towards the production of an editing system for advertising films, with a view to the production of lean versions, strictly comprised of aspects with highlighted valence and salience, (9) develop and apply a neuropsychological instrument able to prediet thc profile of consumers, by means of an online software coupled to an automated system to expom, filter and perform elementary analysis of the database; and (l0) produce correlation studies between the various lindings, with a view to optimising the Marketing and Behavioural Economics strategies, with focus on the neural toolkit. To meet the proposed objective we choose to work from data trianguIation, involving different observatory units : Eight focus groups (11:3 l ), indepth interviews (11 = 2), development and implementation of a survey through an interface line (11 Z 339), applying the scale narcissism NIP 40(11=3O) an experiment 10 capture data from peripheral neurophysiology through eye tracking (n : 30), an experiment to capture data from central and peripheral neurophysiology, involving electroencephalogram (EEG) , measuring heart rate variability (HRV) and galvanic skin response (GSR) (n : 40). The analytical unit covers the automotíve market, three make/models of vehicles Fiat Bravo. Ford Focus and Hyundai I30. Among the findings of qualitative steps, it is possible to infer that, as anticipated by the literature, these are not good measurements for the launching of new products, especially due to the difficulty for the participants to highlight attributes specific to the object under study. By means of an on line survey, it was possible to arrive at a profile for the owner of each vehicle studied, contributing to the literature related constructs in building models to be analysed as posteriori. Online survey findings have been correlated with findings originated from the focal groups, whose methodological advance was revealed through the use of neuropsychological tests such as performance covariates. ln parallel, distinct neurophysiological markers (EEG, HRV and GSR) were simultaneously employed to compare the three car commercials (n : 40), while eye trackíng was employed to explore convergences and dífferences between standardised images of three vehicles (n = 30). The neurophysiological analysís confirmed the superiority of the EEG compared to the peripheral methodologies for discriminating preferences, neural signatures well established in the literature, which rendered reliable findings (p : 0.05). Still ou the analysis of central physiology, some inferences about the activation partem are relaied to the level of engagemem that certain stimulus can promote, opening new perspectives for investigation. Eye tracking findings, associated with data obtained from the verbal determinatíon of preference, revealed a vvay to comprehend the specific Component that makes people prefer 2 car over others, despite their generalised inability to pinpoint the reason. Together, these results highlight that the association between innovative and traditional methodologies allows the production of deeper and more stratcgic results than any of these approaches considercd in isolation.